Contribution of Science, Technology and Society education to the initial training of the agronomist - Castellanos Yero, Odmara María; Buchaca Machado, Deibis; Hernández Alegría, Antonio Vicente (Transformación, 2024)
Objective: The studies of Science, Technology and Society (CTS) help to broaden the perception of the community, as well as the conditions and implications of research and scientific and technological development. The article aims at presenting notions related to the curricular arrangement of CTS education in the agronomy career. Methods: The documentary study and the critical analysis of the sources for the curricular arrangement proposed for the agronomy career were used. Results: The paper suggests notions, styles, dimensions and potential of integration of CTS education from the main discipline of Agricultural Production providing students with a culture of sustainability ethics, and a sound review of the initial training of the Agronomist. Conclusion: The notions that are contributed make it possible to increase the quality of the teaching-learning process of the main integrating subjects of the curriculum based on CTS education.